Kualitas Audit, Profitabilitas, Leverage dan Manajemen Laba Riil - Hermalia Jelita Putri; Cahyani Nuswandari (Universitas Pendidikan Ganesha, 2021)
Financial report is a presentation of the financial performance of an entity/company. Performance information is needed to make potential changes in economic resources that can be controlled in the future. The purpose of this study is to test whether there is an effect of audit quality, profitability, and leverage on real earnings management. This type of research includes quantitative research using secondary data obtained from the company's financial statements. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. Sampling used the purposive sampling method with the criteria of manufacturing companies that were not delisted during the year of observation, namely 2017 to 2019, the company had an annual report from 2017 to 2019. The sample was selected according to the criteria obtained by 113 companies. The data analysis method used SPSS 25. The results showed that audit quality and leverage had no effect on real earnings management, while profitability had a significant positive effect on real earnings management.